Determination of glycolic acid in natural seawater by liquid chromatography coupled with triple quadrupole mass spectrometry. (8th May 2017) - Hong, Haizheng; Li, Weiying; Li, Xiaolin; Huang, Bangqin; Shi, Dalin
Abstract: Glycolic acid, which is produced during photorespiration, is one of the major components of dissolved organic matter released by phytoplankton, comprising up to 40% of their daily primary productivity. However, the sensitivity of existing methods does not allow for accurate measurement of glycolic acid levels in oligotrophic seawater. In this study, we present a straightforward, robust, and sensitive liquid chromatography‐mass spectrometry (LC‐MS) method to quantify glycolic acid in natural seawater following liquid‐liquid extraction, requiring only a small sample size (25 mL seawater). The method has a highly sensitive detection limit of 9 nM, at least fivefold lower than existing methods. This approach was successfully applied to the analysis of seawater samples collected from both eutrophic and oligotrophic marine environments. The results showed that glycolic acid concentrations in natural seawater are positively correlated with chlorophyll a concentrations, indicating that phytoplankton contribute significantly to glycolic acid production in marine environments. As glycolic acid is an important carbon and energy source for marine bacteria, the method developed within this study allows further investigation into the rates of its release and uptake by phytoplankton and heterotrophic bacteria, respectively, as well as the role it plays in phytoplankton–bacteria interactions.